Sporotrichosis in an HIV-positive man with oral lesions: A case report - Fontes, Patrícia Campos; Kitakawa, Dárcio; Carvalho, Yasmin Rodarte; Brandão, Adriana Aigotti Haberbeck; Cabral, Luiz Antonio Guimaraẽs; Almeida, Janete Dias [UNESP] (Karger Publishers, 2007)
Background: Sporotrichosis is a granulomatous fungal infection caused by Sporothrix schenckii, which frequently causes cutaneous or lymphocutaneous lesions and rarely has oral manifestations. Case: A 38-year-old, white, HIV-positive man complained of a 5.0-cm, symptomatic, ulcerated lesion with thin, superficial granulation in the soft palate extending to the uvula. Exfoliative cytology of this oral lesion showed chronic granulomatous inflammatory alterations and extracellular fungal structures consisting of periodic acid-Schiff-positive budding cells and spherical or elongated (cigar bodies) free spore forms. Conclusion: The clinical and cytologic findings allowed the diagnosis of sporotrichosis, demonstrating the importance of cytodiagnosis in fungal diseases. © The International Academy of Cytology.
Keywords: HIV; HIV-related opportunistic infections; Mouth diseases; Sporotrichosis; amphotericin B; itraconazole; adult; case report; cytodiagnosis; granulation tissue; human; Human immunodeficiency virus infection; male; mouth lesion; palate; priority journal; skin defect; soft palate; sporogenesis; Sporothrix schenckii; sporotrichosis; symptomatology; Adult; Epithelial Cells; HIV Seropositivity; Humans; Male; Mouth Diseases; Mouth Mucosa